The Austrian Act on the Protection against Domestic Violence - Dearing Albin (Temida, 2002)
The past few years have seen a fundamental and broadly based change in the response to domestic violence perpetrated by men against women. The Act on Protection against Domestic Violence which entered into force on May 1st, 1997 reflects this new orientation, or rather this shift in paradigm, which has led to a new understanding of the phenomenon of domestic violence and defines appropriate response by the state by it. The impact of this shift in paradigm is considerable: not only have public authorities and private women’s institutions changed their attitudes towards domestic violence, but the general public now responds to this phenomenon in a manner that is entirely different from what it was prior to the approach. Reports on cases of violence no longer merely state the facts indifferently, but now invariably end with the question whether the authorities had been informed and whether they had taken any action to prevent the crime. Thus the public authorities have come to assume responsibility for combating domestic violence as a result of societal developments.